Development of regenerative braking in an electric vehicle using a neural controller with an auxiliary power system - Ahmad Alhamood Alarefe; SALAM ALI MAHMOUD; RAED ALCHAREA (مجلة جامعة دمشق للعلوم الهندسية)
Electric vehicles (EV) have recently spread because of their benefits, such as reducing pollution, as they are environmentally friendly because they use clean energy instead of fossil fuels. The braking system in EV is considered one of the most important systems studied and under development in many researches. It has a significant impact on the stability of the performance of the electric vehicle, and a great benefit in increasing the battery life of the electric vehicle, by recharging it through regeneration braking, and maintaining a large state of charge relatively.